RAINWATER RUNOFF TREATMENT USING LAYERED ECO PAVING BLOCKS: EFFECTS OF THICKNESS AND DENSITY - Ritnawati Ritnawati; Ahmad Qasim Akbar; Mursyid Hasnawi; La Ode Agisaqma; Muh Subri Basri; Fithrah Faradhiba Shalihah; Aisyah Mardiana Ali; Hajerah Hajerah; Ibrahim Djamaluddin; Anugrah Anugrah; Poppy Indrayani; Erdawaty Erdawaty; Xuepeng Zhang (Universitas Trisakti, 2025)
Aims: This study aims to investigate the effect of binder variations on the compressive strength of eco paving blocks composed of four layered materials-rice husk, quartz sand, gravel, and activated carbon-each with a thickness of 6 cm. Methodology and results: The application is directed toward wastewater treatment using the rain garden method. Laboratory experiments were conducted to obtain reliable performance data. The results show that cement-bonded paving blocks demonstrate superior performance compared to those using fly ash binders. Cement adhesives ensured strong cohesion between layers, with blocks maintaining integrity during demolding without signs of damage or porosity. In contrast, paving blocks with fly ash binders required longer drying times due to the high moisture absorption of quartz sand, and they exhibited brittleness caused by weak adhesion. Extended curing was necessary before fly ash could adequately bond the base materials. Conclusion, significance and impact study: Quantitative findings revealed that paving blocks with cement adhesives achieved an average compressive strength of 836.25 MPa, higher than the 696.25 MPa of fly ash-bonded blocks. These results imply that cement remains the more effective binder for eco paving blocks in rainwater runoff and wastewater treatment, while fly ash requires optimization to improve its bonding performance. Eco-paving provides a nature-based, sustainable, and cost-effective solution for urban wastewater management, achieving both structural durability and effective pollutant removal.